O lugar do sujeito feminino na revista curitibana A Sempre-Viva (1924-1925) - Rossigali, Rossana (My University, 2018)
This work discusses the literary production of women in the magazine A Sempre-Viva, published in Curitiba, in 1924/1925. There is an investigation about the place of the feminine subject in this publication, based on Gender Cultural Studies. In order to accomplish that goal, it was necessary to study the history of western women, which explains the reasons for their submission over the centuries, as well as the feminism, which explains how they reacted to that domain. Furthermore, the history of the press – feminine and feminist – was also analysed. In Brazil, it is closely related to literature. The few female writers who succeeded in publishing were fighting the rules, which were very strict, keeping women only in private places. That is why many writers used pseudonyms. At the end of the work it is possible to conclude that the magazine organizers themselves were forgotten.
No presente trabalho, discute-se a produção literária de mulheres na revista curitibana A Sempre-Viva, publicada em 1924/1925. Assim, investiga-se que lugar o sujeito feminino ocupa nessa publicação, a partir de aportes teóricos dos Estudos Culturais de Gênero. Para cumprir tal objetivo, foi necessário perscrutar a trajetória histórica da mulher ocidental, a qual explica os motivos que a levaram a exercer um papel submisso ao longo dos séculos, bem como o feminismo, que elucida os caminhos da reação a esse domínio. Além disso, investigou-se o percurso da imprensa – aí incluída a feminina e a feminista –, a qual, no Brasil, guarda estreita relação com a literatura. As poucas mulheres que conseguiam publicar confrontavam as normas vigentes, que as circunscreviam ao âmbito privado, o que fez da utilização de pseudônimos prática corrente. Constata-se, ao final do trabalho, que as próprias organizadoras da revista, que tanto lutaram pelo resgate de escritoras desconhecidas, sucumbiram ao esquecimento.
Keywords: Mulheres na literatura; Escritoras - Brasil; Feminismo; Women in literature; Women authors - Brazil; Feminism